Pedagogical performance in the preschool teaching of students with Autism Spectrum Disorder - Rocha,Eduardo Pimentel da (2021)
ABSTRACT Purpose: to describe the panorama of the pedagogical context in the preschool teaching of students with Autism Spectrum Disorder (ASD), in a municipality in the state of São Paulo, Brazil. Methods: 32 teachers, including early childhood education (ECE), special education (SE), and specialized educational assistance (SEA), participated answering a questionnaire about their performance with autistic students. A descriptive qualitative analysis of the data was performed. Results: the average age of the teachers was 40.6 years old, with an undergraduate degree in Teaching, Pedagogy, Special Education, and/or Visual Arts, of which 84.4% were postgraduate. 87.4% knew ASD characteristics; 80%, SEA, 66.7%, SE, 57.1% of ECE teachers had receive the medical report. 78.1% reported difficulties in socialization, communication, behavior, learning; 15.6%, aggressive behavior / irritation; 12.5%, difficulties in attention / concentration; 6.2%, motor coordination difficulties in their autistic students. 62.5% considered that their autistic students had the potential to follow mainstream education; 68.8% received guidance from team professionals; 78.1% participated in courses/lectures on the theme; 28.1% considered they were able to teach autistic children; 78.1% stated that adjustments in the teaching structure were necessary. Conclusion: the scenario of the pedagogical context in the preschool teaching of students with ASD, in the studied municipality, needs reflections. Information on ASD characteristics, training courses, knowledge on individual follow-ups, so that teachers are prepared to promote effective teaching and learning, are needed.